METHOD DEVELOPMENT AND VALIDATION OF IRBESARTAN CHLORTHALIDONE AND CILNIDIPINE IN THEIR COMBINED TABLET DOSAGE FORM BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Dagariya, Rishabh K; Jat, Rakesh K (Journal of Drug Delivery and Therapeutics, 2017)
The present work describes a validated reverse phase high performance liquid chromatographic method for simultaneous estimation of Irbesartan chlorthalidone and cilnidipine in tablet dosage form. The quantification was carried out using C18 column (250 x 4.6mm, 5Î¼m) and mobile phase comprised of Buffer, Acetonitrile and TEA in a proportion of 80:20:0.1 %v/v/v. The flow rate was 1.0 ml/min and the eluent was monitored at 222 nm. The selected chromatographic conditions were found to effectively separate Irbesartan Chlorthalidone and cilnidipine were 3.807 min, 4.667 min, and 6.887 min respectively. Linearity was found to be in the range of 30-90 Î¼g/ml, 1.25-3.75 Î¼g/ml and 1-3 Î¼g/ml for Irbesartan Chlorthalidone and cilnidipine respectively. The percentage recoveries of all the drugs were found to be 99.27-99.81%, 99.57-99.99% and 99.22-99.44% for Irbesartan, chlorthalidone, and cilnidipine. The proposed method was found to be fast, accurate, precise, and reproducible and can be used for simultaneous estimation of these drugs in a tablet.